Psychometric Properties of the Communication Skills Attitudes Scale (CSAS) among Portuguese undergraduate students in Allied Health Sciences - Carvalho, Irene (2015)
Communication in health has attracted increasing interest in recent decades, revealing the need for appropriate research tools. The study of the psychometric properties of instruments and the confirmation of their structure is crucial for the reliability and validity of the overall results of scientific work. Repeated analyses of these dimensions over time are important because it allows us to identify changes that result from social and cultural changes. This study aims to assess the reliability, factor structure, and construct validity of the Communication Skills Attitudes Scale.